(3GdOQGc ajeG jJYdb HGdShGcs - (3LYaQ Hf GOQjS GdcJGfjs
(3ChdgG (B:s
(3hHYO aEf GdShGc ef Sei GdeQSdjf s
(3BNQgG (B:s
(3Efg ai GUWdGM GdYdeGA GSJYeGd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3CUhd Gdabgs